Effects of Combined Inoculation of Azospirillum and AM Fungi on the Growth and Yield of Finger Millet (Eleusine coracana Gaertn) Var. Co 12 - K. Ramakrishnan2*, M. Ezhil Bama1 and (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> An experiment was conducted to find out the effect of Azospirillum and AM (Arbuscular mycorrhizae) fungi on finger millet (Eleusine coracana Gaertn) var. Co 12.Â  Both the inoculants were applied by seed, seedling and soil application method. These inoculants were tried at as a single and dual inoculation and comprised with nitrogen and phosphorus controls. Over all influences by these two beneficial microbes played a vital role in supplying N and P to the finger millet and found enhanced the growth and yield over the untreated control.